PENGARUH STRATEGI PQ4R DALAM PEMBELAJARAN MEMBACA PEMAHAMAN TEKS BAHASA JEPANG PADA LEVEL CHUUKYUU - Meiggi Mawarni; Sri Wahyu Widiati; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to find out the influence of students’s ability in reading comprehension japanese text (dokkai) after using PQ4R strategy. This research is a weak-experiment type one group pretest post test design. The object of this research is 12 third-level students as the responsents. Data collection was performed by giving test. The given test was (pretest and post test). The given test was 10 essai to find out the students’s ability in reading comprehension (pretest and post test). This research is processed by paired sampling t-test using software of SPSS Version 19 to get the value of the significant. Based on the data analysis, the value of the post test is lower than 0,05 (0,000<0,05), It means that Ha is accepted and Ho is rejected, so there is a significant impact with the application on PQ4R strategy on the learning of Japanese reading comprehension (dokkai) by the third level students of Japanese Education Department Faculty of Teacher’s Training and Education Riau University. Thus, it can be concluded that strategy PQ4R was effective in reading comprehension japanese text (dokkai).Key Words: Dokkai, Strategy, PQ4R